Rules, constraints, and phonological phenomena - Nevins, Andrew; Vaux, Bert. (Oxford : Oxford University Press, 2008)
Written by prominent phonologists, this title goes to the heart of debates in phonological and linguistic theory: should the explanation of phonological variety be constraint or rule-based and, in the light of that answer, how in the mind does phonology interface with other components of the grammar.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constraints (Linguistics); Grammar, Comparative and general -- Phonology; Linguistic analysis (Linguistics); Order (Grammar)